Using CBPR to address health disparities with the Marshallese community in Arkansas. (3rd April 2018) - McElfish, Pearl A.; Moore, Ramey; Laelan, Melisa; Ayers, Britni L.
Abstract: Context: Arkansas currently has the largest Marshallese community in the continental US. The limited research available demonstrates that Marshallese have significant health disparities, with higher rates of obesity, diabetes, cardiovascular disease and infectious diseases than the US population. Objectives: The purpose of this paper is 2-fold: (1) to describe the formation and capacity building efforts of a community-based participatory research partnership with the Marshallese community in Arkansas and (2) to describe key findings and lessons learned from 5 years of collaborative research. Methods: A community-based participatory research approach was implemented to build alliances and improve health disparities in a Marshallese community. Results: Overarching lessons learned from collaboration with the Marshallese community include the: (1) Intensive involvement of Marshallese from multiple sectors of the community and in multiple roles in the research process, (2) Importance of interprofessional teams, (3) Importance of church, (4) Consideration of sex, (5) Importance of family and definition of family, (6) Talk Story and qualitative methods and the (7) Importance of cultural humility. Conclusions: This research helps fill important gaps in documenting the health disparities and interventions to address those disparities in the Marshallese community.